1152 INVESTIGATION ON THE HIGH INCIDENCE OF THE ATTRV-CAUSING TRANSTHYRETIN VARIANT VAL142ILE IN CENTRAL ITALY. (15th December 2022) - Cappelli, Francesco; Argiro´, Alessia; Zampieri, Mattia; Giotti, Irene; Boschi, Beatrice; Frusconi, Sabrina; Buxbaum, Joel; Gennarelli, Massimo; Polimanti, Renato; Olivotto, Iacopo; Perfetto, Federico; Mazzarotto, Francesco
Abstract: The p.Val142Ile variant in transthyretin (encoded by the TTR gene) is the most common genetic cause of transthyretin-related amyloidosis. This allele is particularly prevalent in communities of African descent compared with populations of different ancestries, where its frequency is two orders of magnitude lower. For this reason, p.Val142Ile has always been considered an "African" variant, with limited studies performed on individuals of European descent. However, recent reports of higher-than-expected prevalence in European-ancestry populations question the African specificity of this allele. Here we show that the high recurrence of p.Val142Ile in central Italy is due to a founder effect and not to recent admixture from African populations, highlighting how this may be the case in other communities. This suggests a probable underestimate of the global prevalence of p.Val142Ile, and further emphasizes the importance of routine inclusion of TTR in gene panels used for clinical genetic testing in hypertrophic cardiomyopathy (independently of the patient's geographical origin), that transthyretin-related amyloidosis can mimic. Figure. Principal Component Analysis (PCA) of the 16 probands together with the 25044 individuals of the 1000 Genomes Project (Phase 3) having been genotyped both within the 1000 Genomes Project (NA10851_1KG) and in-house (NA10851_internal). The proband clustering within the smear of native Americans is A228.